(untitled) (Pulse, 2026)
The coexistence of beta thalassemia trait (also known as heterozygous beta thalassemia, HBT) and polycythemia vera (PV) is extremely rare, with only a few cases reported in medical literature. This combined condition is significant because the two disorders have opposing effects on hemoglobin (Hb) and hematocrit (Hct), which can mask the presence of each other and delay diagnosis. Missing or delaying the diagnosis of PV can lead to deleterious effects due to the high risk of thrombosis. We present a case of an elderly male whose diagnosis of PV was delayed due to the coexistence of HBT and other comorbidities, and review the relevant literature. Pulse Volume 17, Issue 2 2025; 34-37